The 40+ entrepreneur : how to start your own successful business in your 40's, 50's, 60's ... and beyond - Goodman, Gary S. (G & D Media, 2018)
"At age 90, Jack Smiley wasn't thrilled with the community in which he retired, so he built his own. Today, it provides him with a net income of $40,000 each month. Famously, KFC's 65 year-old Kentucky Colonel Harlan Sanders supplemented a paltry Social Security check by franchising his unique recipe for fried poultry. Past 50, McDonald's Ray Kroc made a similar trek in multiplying by many thousands a few popular, golden-arched hamburger stands from San Bernardino, California. Contrary to popular mythology, entrepreneurship is NOT spearheaded mostly by baby-faced, technology-savvy, post-adolescents whose brands include Facebook and Apple. According to a recent study, fully 80 percent of all businesses are started-up by people over 35"--